A virtual backoff algorithm-based MAC protocol for underwater acoustic sensor networks. (2016) - Gaffar, H. Abdul; Krishna, P. Venkata
Underwater acoustic sensor networks (UASN) is different from terrestrial sensor networks. Designing medium access control (MAC) protocols are challenging task in UASN. In this paper, we proposed a new MAC protocol for underwater communication which is called as underwater virtual backoff algorithm-based medium access control (UVMAC). This UVMAC approach is based on virtual backoff algorithm (VBA). The UVMAC is an enhancement of the VBA method that avoids collision during medium access in wireless networks. UVMAC reduces the number of collisions and increases the throughput of the network. In UVMAC, the sensor nodes are limited to access the channel in terms of sequence number. The simulation results show that the proposed UVMAC are performed well compared to reservation medium access control (RMAC) and broadcast MAC for UASN.